(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
A comparative analysis of the vibrational spectra of synthesized complex metal compounds and a non-coordinated ligand - imidazole - was carried out. As a result, it turned out that the stretching frequencies n(C=N) are shifted by 10-35 cm-1 to the high-frequency region, which indicates the coordination of imidazole in metal complexes through one of the two imidazole ring’s nitrogen atoms. Moreover, the spectra of chloride, sulfate, and nitrate complexes of Cu, Ni, Zn, and Cd were compared with the spectra of nitrate complexes Mg and Ca, which confirmed the assumption of monodentate coordination of the ligand with the central atom only through the imidazole ring’s pyridine nitrogen atom.